Participating Unequally? Assessing the Macro-Micro Relationship between Income Inequality and Political Engagement in Europe - Andrea Filetti (Coordinamento SIBA, 2016)
A great deal of attention has been paid to the consequences of economic inequality on political participation, yet only few empirical studies address the macro-micro relationship between income in-equality and individual engagement. Furthermore, empirical indications diverge and give rise to competing theoretical arguments to be tested. This article seeks to fill this gap and to do so by using the latest round of the European Social Survey (ESS). The contribution is twofold: on the one hand, it establishes a direct link between measures of economic and political inequality - albeit of a particular type. On the other, it provides an up-to-date picture on participatory trends in Europe. In more details, income inequality is found to depress overall political participation and, most importantly, to increase the participatory gap between rich and poor for all unconventional forms of engagement.